Pengembangan Aplikasi Pencarian Riwayat Percakapan Costumer Care (Studi Kasus: PT Beon Intermedia) - Yusuf Ramadhani; Adam Hendra Brata; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT Beon Intermedia is a company provides website hosting services based in Indonesia. The company focused to costumer satisfaction and they are well aware how significant costumer is. In the interest of intensify the customer, they consistently analyze customer problem. To analyze the problem customer encounter. They utilize chat data from Customer Care, which is customer care division are the only one to deal with the customer. From data chat can be discovered problem like obstacle and complaint about the services. By analyzing customer care's chat the company expected to found out the services could be improved. To ease analyze process by company the search engines is needed. Search chat with proper result can accelerate the process. In this research, the search chat application will be developed. The search chat application implement Cosine Similarity which measure similarity between query inserted and chat. The calculation of similarity will be measure proximity the vectors. The vectors represent chat and query as a reference. For compute chat as a vector, which is text based. The application will be weighted the text using TF - IDF method. The application is website based. Result of this research is search engines. To assure the accuracy of search engine, this research will be test with accuracy test. Accuracy test has two cases with different query. The result for first test case is 80% accuracy and the second case is 60% accuracy.